Whole-exome sequencing identifies recurrent AKT1 mutations in sclerosing hemangioma of lung - Jung, Seung-Hyun (Proc Natl Acad Sci U S A, 2016)
Pulmonary sclerosing hemangioma (PSH) is a benign tumor with two cell populations (epithelial and stromal cells), for which genomic profiles remain unknown. We conducted exome sequencing of 44 PSHs and identified recurrent somatic mutations of AKT1 (43.2%) and β-catenin (4.5%). We used a second subset of 24 PSHs to confirm the high frequency of AKT1 mutations (overall 31/68, 45.6%; p.E17K, 33.8%) and recurrent β-catenin mutations (overall 3 of 68, 4.4%). Of the PSHs without AKT1 mutations, two exhibited AKT1 copy gain. AKT1 mutations existed in both epithelial and stromal cells. In two separate PSHs from one patient, we observed two different AKT1 mutations, indicating they were not disseminated but independent arising tumors. Because the AKT1 mutations were not found to co-occur with β-catenin mutations (or any other known driver alterations) in any of the PSHs studied, we speculate that this may be the single-most common driver alteration to develop PSHs. Our study revealed genomic differences between PSHs and lung adenocarcinomas, including a high rate of AKT1 mutation in PSHs. These genomic features of PSH identified in the present study provide clues to understanding the biology of PSH and for differential genomic diagnosis of lung tumors.